KEMAMPUAN BERPIKIR KRITIS SISWA SMP NEGERI 1 JENU BERDASARKAN LANGKAH FACION PADA POKOK BAHASAN JAJARGENJANG DAN TRAPESIUM - Edy Nurfalah; Yuni Afifah (Jurnal Riset Pembelajaran Matematika, 2019)
Each student has a different level of critical thinking ability, while critical thinking is a basic ability that students must possess. The purpose of this study is to describe students' critical thinking skills based on Facion steps on the subject lines and trapezoidal. This research is a descriptive study using quantitative and qualitative data. The research instrument used was in the form of critical thinking ability test questions and interview guidelines. The research subjects used were 32 students while the study sample analyzed the data as many as 3 students who entered the 3 categories of high, medium, and low critical thinking skills. The data analysis technique used in the form of descriptive statistical data analysis developed based on indicators of thinking, namely interpretation, analysis, evaluation, and inference. The results of this study indicate that students' critical thinking skills based on Facion steps on the subject line and trapezoid class VII-D SMP Negeri 1 Jenu 2017/2018 school year are generally in the low category with an average score of 64.82.